Measuring the public acceptance of urban congestion-pricing: a survey in Melbourne (Australia) - Liu, Zhiyuan; Shiwakoti, Nirajan; Bie, Yiming (Transport, 2018)
The practical implementations of congestion-pricing are largely restricted, due to the low public acceptance level. Based on a field survey, this study reveals the public acceptance level in Melbourne, Australia. It was found that the level of acceptance for a new congestion-pricing scheme is 42%, which still needs to be improved if a congestion-pricing scheme is to be implemented. Some strategies are proposed and discussed to increase the acceptance level towards congestion charge in urban cities, including an information campaign, public transport improvements and a trial.First Published Online: 29 Mar 2016